Improving Emotional Control And Activities of Daily Living (ADL) of Patients with Schizophrenia Using Spiritual Mindfulness Through SI-DEPAPU Application - Meidiana Dwidiyanti; Ainun Najib Febryna Rahman; Dessy Dwi Cahyaningrum; Diyan Yuli Wijayanti (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Schizophrenia is a major mental health problem in the world that requires more attention. Patients with schizophrenia are at higher risk of poor psychological well-being and violent behaviors as expression of anger and delusion. Mindfulness alone is considered less efficient so it needs to be developed with technology, as such further technological development regarding its application is needed.Objective: This study aimed to determine the effects of spiritual mindfulness intervention through the SI-DEPAPU application on the ability to control anger and perform activities of daily living (ADL) among schizophrenic patients.Methods: This study used a pretest-posttest quasi-experimental design with a control group. The samples were 60 schizophrenic patients randomly selected and divided into two groups. The intervention group was given four sessions of mindfulness in two weeks through the SI-DEPAPU application. This study used the anger management ability questionnaire developed by Sadipun et al. (2018) to measure the patient's ability to control anger and the North American Nursing Diagnosis Association (NANDA) questionnaire by Wilkinson (2016) to measure ADL. The instrument was tested for its validity among 20 schizophrenic patients with a risk of violent behaviors, and the results were valid and reliable in which the r-count r-table (0.444), the control group was given standard hospital care.Results: The results showed that the patient’s ability to control anger and perform ADL increased with p=0.000 and p=0.005, (p = 0,000 0,05) respectively. The intervention group had a higher mean score than the control group.Conclusion: Mindfulness spiritual interventions through the SI-DEPAPU application could help schizophrenic patients control anger and increase their ADL.